MENCIPTAKAN GENERASI YANG BIJAK DALAM PENGGUNAAN MEDIA SOSIAL - Yesi Wening Sari (Islamic University of Indonesia, 2019)
Times will quickly change as the culture development. Indonesia is famous for its plurality, with various colors ranging from regional origin, language, tradition, and no less importance of belief. The beauty of Indonesia creates attraction for foreigners, so many come to explore just to learn Indonesian culture. Culture language is derived from Sanskrit buddhayah from the word of mind means the mind or reason, got the sense by Koentjaraningrat said that culture is the power of creativity, intention, and taste, when added the prefix